Thyroxine-Induced Absences in JME - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A patient with juvenile myoclonic epilepsy (JME), manifested as absences at age 10 and myoclonic jerking and generalized tonic clonic seizures at age 15, was treated successfully with primidone at the King Fahad National Guard Hospital, Riyadh, Saudi Arabia.